TANGGUNG JAWAB HUKUM PENYELENGGARA TERHADAP KONSUMEN AKIBAT PEMBATALAN KONSER MUSIK - Kartika, Avrillia Cindy; Susanti, Erna; Hediati, Febri Noor (Jurnal Ilmiah Advokasi, 2025)
Currently, the organization of music concerts requires careful planning and coordination. However, in practice, unilateral cancellations by organizers still frequently occur, causing losses to consumers. This study aims to analyze the elements of unlawful acts and the forms of legal protection available to consumers in cases of unilateral concert cancellations. A normative juridical approach is employed in this research by examining the provisions of Article 8 letter f of Law Number 8 of 1999 on Consumer Protection and Article 1365 of the Indonesian Civil Code. The findings indicate that concert cancellations without valid justification can be classified as unlawful acts. Concert organizers are obliged to provide compensation to consumers in the form of damages. The legal protection afforded is based on the principles of justice and the responsibility of business actors. This study highlights the necessity of including consumer protection clauses in concert contracts and strengthening dispute resolution mechanisms that are both swift and fair.Keywords: Consumer Protection; Unlawful Act; Music Concert; Compensation; Consumer Protection Law.